Additional Benefits of Creatine Monohydrate Supplementation on Muscle Strength, Muscle Mass Gain and Training Performance - A Systematic Review - Tadeusz Kuźnieców; grzegorz Karaban; Monika Paszkowska; Klaudia Mularczyk; Michał Borawski; Aleksandra Ciuła; Anna Jakubiak; Joanna Miśkiewicz; Patrycja Znamirowska; Magdalena Kupis (Quality in Sport)
Introduction: Creatine monohydrate is one of the most researched and tested supplements in sport known for its benefits on muscle strength, muscle mass gain and training performance. This systematic review synthesizes evidence from various studies to evaluate the impact of creatine monohydrate supplementation on the following outcomes.